Truth about managing people and nothing but the truth - Robbins, Stephen P. (Prentice Hall Upper Saddle RiverUS, 2002)
Targets practising and aspiring managers. Aims to provide insights into managing people at work and covers 63 topics including: hiring, motivation, leadership, communication, building teams, conflict management, coping with change, and performance evaluation.